Establishment and Characterization of St Louis Encephalitis Virus Persistent Infections in Aedes and Culex Mosquito Cell Lines - Randolph, Valerie B.; Hardy, James L. (Journal of General Virology, 1988)
Summary Persistent infections with St Louis encephalitis (SLE) virus were established in three mosquito cell lines (Aedes albopictus, A. dorsalis and Culex tarsalis) and were maintained for over 2 years. All three persistently infected cell cultures shared two features: (i) no overt cytopathic effect and (ii) a relatively high proportion of cells infected (41 to 85%). The Aedes persistently infected cultures were resistant to superinfection with the homologous virus but not heterologous viruses. Two significant differences were observed between the Aedes and C. tarsalis persistently infected cell cultures: (i) viral titres in the A. albopictus and A. dorsalis cell cultures decreased slowly over time (the decrease was particularly marked in the A. albopictus cell cultures), whereas titres in the C. tarsalis cell cultures remained relatively constant and (ii) the addition of anti-SLE virus antibody led to decreased virus production in the C. tarsalis cell cultures (one of two cultures was cured of infection), whereas antibody had no effect on the persistently infected Aedes cell cultures. These results suggest that there may be significant differences in the regulation of viral replication and the maintenance of flavivirus persistent infections in mosquito cell lines of different origins.
Keywords: persistent infections